The Semiotic System and Structure Of Language - Khavaskhon Shokirova (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This study explores semiotics as the study of sign systems, analyzing the relationship between language, reality, and cognition. The research aims to examine how linguistic signs function within semiotic structures and how they contribute to meaning-making. A theoretical approach is used, incorporating linguistic and semiotic analysis from major scholars like Saussure and Peirce. The findings highlight the interdependence between language and semiotic systems, demonstrating that linguistic structures play a crucial role in shaping human perception and communication.